Omnichannel retailing: a tale of three sectors - Santiago Iglesias-Pradas (Taylor & Francis Group, 2021)
Accelerated by the COVID-19 pandemic, the long-anticipated digital transformation of traditional retail has become the new reality. Retailers are responding to changes in consumers’ shopping behaviours and their demand for new interaction channels and touchpoints to shop at their convenience, regardless of time and location. Consequently, retailers are experiencing a change from single-channel models to multi-channel and omnichannel models. Omnichannel retailing demands integrated channel management and operation to improve customers’ shopping experiences. This study uses measures of channel integration levels from previous research to analyse channel integration among leading vendors in three top retailing sectors (clothing and apparel, home furniture and grocery) and expands the analysis by including indicators of digital transformation. The model includes 27 indicators related to channel integration and 9 indicators of digital transformation, and compares the results across sectors. By so doing, the study also aims to help establish values that may be used as target or reference values of channel integration and digitalization of retailers across sectors, irrespective of their size. The research methodology uses the 'mystery shopper' technique and includes the collection of data about the 165 leading companies in these sectors in Spain.